Building the case for entrepreneurship and the use of digital technology for agricultural development in Egypt - Aglan, Fatma El Zahraa (2019)
As part of the IFPRI Egypt Seminar in partnership with the World Bank, IFPRI Egyprt seminar “Innovations for Agricultural Development in Egypt”.